Komunikasi Pariwisata Berbasis Kearifan Lokal Dalam Mengembangkan Potensi Wisata Di Situ Lengkong Panjalu - Ai Yulianti; Hasim Hasim (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The purpose of this study is to determine how effective tourism communication is in influencing the level of tourist visits, focusing on the management of the Situ Lengkong Panjalu tourist attraction. Tourism communication is considered an important element in the exchange of messages between marketing agencies and tourism stakeholders. This study uses qualitative descriptive research methods to understand the phenomena experienced by research subjects, especially in conveying messages based on local wisdom that attracts tourist visitors. The results showed that the manager of Situ Lengkong Panjalu tourist attraction emphasized local wisdom in its promotional message, involving aspects of geography, history, and beauty of Situ Lengkong Panjalu. Although promotion through social media has not been optimal, information is still conveyed through the Village's website and social media accounts. The conclusion of this study highlights several aspects, including tourism communication sources, main objectives of communication, the role of culture in tourist attraction, reinforcing local values, limitations of digital promotion, direct promotion efforts, tourism communication strategies, and internal barriers in promotion.